Accuracy of lutetium-177 SPECT activity quantification and patient-specific dosimetry: a Monte Carlo study - Ramonaheng, Keamogetswe (University of the Free State, 2021)
The goal of radiopharmaceutical therapy (RPT) is to deliver the maximum dose to cancerous tumours while sparing healthy tissue. Ideally, the radiopharmaceutical should accumulate in the tumorous tissue and the radiation entirely absorbed for tissue destruction; however, this is not the case. Dosimetry strives to balance the efficacy of delivering the maximum dose to the tumour cells with minimal toxicity to the healthy tissue. Patient-specific dosimetry offers the potential for RPT to reach its full potential as a powerful precision-based treatment. Efforts for patient-specific dosimetry remain a challenge due to the steps involved in the clinical dosimetry workflow. SPECT/CT imaging allows the estimation of the bio-kinetic distribution of the radiopharmaceuticals with good precision, which is required for accurate dosimetry. Different dosimetry software is available (commercial and non-commercial), but these should be benchmarked before being used. Optimising the imaging process for activity quantification and dosimetry in the NM discipline is essential, and Monte Carlo (MC) techniques have been used successfully in this endeavour. Furthermore, full MC dosimetry gained wide acceptance as the gold standard and the most accurate means for patient-specific dosimetry. MC simulations offer the advantage of having a gold standard against which the dosimetry can be benchmarked, and the dosimetry accuracy evaluated. Therefore this thesis aimed to assess the accuracy of 177Lu SPECT activity quantification and patient-specific dosimetry using MC simulations. The focus was on the bio-distribution of 177Lu- DOTATATE due to its clinical relevance in RPT of patients with metastasised neuroendocrine tumours. The kidneys are the dose-limiting organs for RPT with 177Lu-DOTATATE. Studies have shown kidney doses to vary significantly between patients. Given the relation between tumour absorbed dose and tumour reduction, for a complete efficacy evaluation, absorbed doses should be determined not only for the kidneys but, where possible, extended to the tumours. This study incorporated voxel-based phantoms generated from phantom and patient CT data to perform virtual image-based activity quantification and dosimetry using MC simulations. The voxel-based phantoms were modified to include spherical structures mimicking tumours. The first objective of this study was to validate a model of the Siemens Symbia T16 dual-head SPECT/CT gamma camera available in our clinic using the SIMIND MC program for 177Lu imaging. The validation was achieved by comparing experimental and simulated gamma camera performance planar and SPECT criteria tests. The results were in good agreement and provided adequate confidence that SIMIND could emulate the Symbia T16 successfully and be used for further investigations of 177Lu SPECT/CT image quantification. The second objective investigated the effect of sphere and cylinder calibration factor (CF) geometries and their corresponding recovery coefficients (RCs) on the quantification accuracy of 177Lu SPECT images using MC simulations. The investigations were performed using geometries of a cylindrical, an anthropomorphic torso, and patient-specific phantoms. The quantification accuracy was evaluated for tumours and the kidneys. The results demonstrated that 177Lu SPECT quantification accuracies compared favourably for sphere-based and cylinder-based CF and RC combinations when all SPECT corrections were applied. The absolute quantification accuracy of ≤ 3.5% compared well to literature findings and complied with the 5% requirements for accurate dosimetry. The third objective of the thesis aimed to compare the accuracy of the absorbed doses computed with the software LundADose and OLINDA/EXM 1.0 using three patient-specific voxel-based phantoms. The dosimetry accuracy was assessed by comparing the computed doses to the “true” activity images combined with full MC dosimetry to define the gold standard. The accuracy between LundADose (6.6%) and OLINDA/EXM 1.0 (8.1%) was comparable. The ≤ 10% dosimetry accuracy suggested that the software platforms approximated the true dose estimates and advocated for the dosimetry accuracy to be reliable.

Die doel van radiofarmaseutiese terapie (RFT) is om kankergewasse met die maksimum dosis te behandel terwyl gesonde weefsel gespaar word. Ideaal-gesproke moet die radiofarmaseutiese middel in die tumorweefsel ophoop en die bestraling heeltemal geabsorbeer word vir weefselvernietiging; dit is egter nie die geval nie. Dosimetrie streef daarna om die doeltreffendheid van die lewering van die maksimum dosis aan die tumorselle te balanseer met minimale toksisiteit vir die gesonde weefsel. Pasiënt-spesifieke dosimetrie bied die potensiaal vir RFT om sy volle potensiaal te bereik as 'n kragtige presisie-gebaseerde behandeling. Pogings vir pasiënt-spesifieke dosimetrie bly 'n uitdaging as gevolg van die stappe betrokke by die kliniese dosimetrie-werkvloei. EFERT/RT-beelding laat die beraming van die bio-kinetiese verspreiding van die radiofarmaseutiese middels met goeie presisie toe, wat nodig is vir akkurate dosimetrie. Verskillende dosimetrie-sagteware is beskikbaar (kommersieel en nie-kommersieel), maar dit moet vergelyk word voordat dit gebruik word. Die optimalisering van die beeldingsproses vir aktiwiteitskwantifisering en dosimetrie in die NM-dissipline is noodsaaklik, en Monte Carlo (MC) tegnieke is suksesvol in hierdie poging gebruik. Verder geniet volledige MC-dosimetrie wye aanvaarding as die goue standaard en die mees akkurate middel vir pasiënt-spesifieke dosimetrie. MC-simulasies bied die voordeel om 'n goue standaard te hê waarmee die dosimetrie vergelyk kan word, en die dosimetrie-akkuraatheid geëvalueer kan word. Daarom het hierdie tesis gepoog om die akkuraatheid van 177Lu EFERT-aktiwiteitskwantifisering en pasiënt-spesifieke dosimetrie met behulp van MC-simulasies te assesseer. Die fokus was op die bio-verspreiding van 177Lu-DOTA-TAAT as gevolg van die kliniese relevansie daarvan in RFT van pasiënte met gemetastaseerde neuro-endokriene gewasse. Die niere is die dosisbeperkende organe vir RFT met 177Lu-DOTA-TAAT. Studies het getoon dat nierdosisse aansienlik verskil tussen pasiënte. Gegewe die verband tussen tumor-geabsorbeerde dosis en tumorvermindering, vir 'n volledige doeltreffendheidsevaluering, moet geabsorbeerde dosisse nie net vir die niere bepaal word nie, maar, waar moontlik, na die gewasse uitgebrei word. Hierdie studie het voxel-gebaseerde fantome geïnkorporeer wat gegenereer is vanaf fantoom- en pasiënt-RT-data om virtuele beeldgebaseerde aktiwiteitskwantifisering en -dosimetrie uit te voer deur gebruik te maak van MC-simulasies. Die voxel-gebaseerde fantome is aangepas om sferiese strukture in te sluit wat gewasse naboots. Die eerste doelwit van hierdie studie was om 'n model van die Siemens Symbia T16-dubbelkop EFERT/RT-gammakamera wat in ons kliniek beskikbaar is, te bekragtig deur die SIMIND MC-program vir 177Lu-beelding te gebruik. Die bekragtiging is bereik deur eksperimentele en gesimuleerde gammakamera prestasieplanêre en EFERT-kriteriatoetse te vergelyk. Die resultate stem goed ooreen en het voldoende vertroue verskaf dat SIMIND die Symbia T16 suksesvol kan naboots en gebruik kan word vir verdere ondersoeke van 177Lu EFERT/RT beeldkwantifisering. Die tweede doelwit het die effek van sfeer- en silinder-kalibrasiefaktor (KF) geometrieë en hul ooreenstemmende herstelkoëffisiënte (HKs) op die kwantifiseringsakkuraatheid van 177Lu EFERT-beelde ondersoek deur gebruik te maak van MC-simulasies. Die ondersoeke is uitgevoer met behulp van geometrieë van 'n silindriese, 'n antropomorfiese torso en pasiënt-spesifieke fantome. Die kwantifikasie akkuraatheid is geëvalueer vir gewasse en die niere. Die resultate het getoon dat 177Lu EFERT-kwantifikasie-akkuraathede gunstig vergelyk vir bol-gebaseerde en silinder-gebaseerde KF- en RT-kombinasies wanneer alle EFERT korreksies toegepas is. Die absolute kwantifikasie akkuraatheid van ≤ 3.5% het goed vergelyk met literatuurbevindinge en voldoen aan die 5%-vereistes vir akkurate dosimetrie. Die derde doelwit van die tesis was daarop gemik om die akkuraatheid van die geabsorbeerde dosisse wat met die sagteware LundADose en OLINDA/EXM 1.0 bereken is, te vergelyk deur drie pasiëntspesifieke voxel-gebaseerde fantome te gebruik. Die dosimetrie-akkuraatheid is beoordeel deur die berekende dosisse te vergelyk met die "ware" aktiwiteitsbeelde, gekombineer met volle MC-dosimetrie om die goue standaard te definieer. Die akkuraatheid tussen LundADose (6.6%) en OLINDA/EXM 1.0 (8.1%) was vergelykbaar. Die ≤ 10% dosimetrie-akkuraatheid het voorgestel dat die sagteware-platforms die ware dosisskattings beraam het en bepaal dat die dosimetrie-akkuraatheid betroubaar is.

Sepheo sa radiopharmaceutical therapy (RPT) ke ho fetisa mothamo o lekaneng ho fihla boemong ba ho hlasela dihlahala tsa mofetshe kapa kankere, e le ho baballa setho se phetseng hantle. Hangata masedi a radiopharmaceutical a lokela ho bokellana ho setho seo se hlasetsweng ke mofetshe mme masedinyana ana a amohelwe ka botlalo e le ho bolaya tlhaselo eo; leha ho le jwalo, mona ha ho jwalo. Tekanyetso ya mothamo e thusa ho lekanya bohlwahlwa ba phethiso ya mothamo oo o feletseng ho ya ho disele tsa tlhaselo eo ya hlahala tse nang le tjhefu hanyenyane ho se fihle sethong se phetseng hantle. Mothamo o lokiseditsweng mokudi ka ho qolleha o fana ka bokgoni ba hore RPT e fihlelle bokgoni ba yona bo feletseng jwaloka pheko e matla e theilweng hodima nako e nepahetseng. Mekutu bakeng sa mothamo o loketseng mokudi ke phephetso e kgolo ho ya ka dikgato tse amehang bakeng sa tshebetso ya tleliniki malebana le tekanyo ya mothamo. Ditshwantsho tsa SPECT/CT di dumella tekanyo ya kabo ya bio-kinetic ya radiopharmaceuticals tse nang le tekanyo e nepahetseng, e leng e loketseng tekanyo ya mothamo. Mefuta e fapaneng ya softewere ya tekanyetso e a fumaneha (ya kgwebo le eo eseng ya kgwebo), empa e lokela ho bapiswa le e meng pele e ka sebediswa. Ho sebedisa tshebetso ya ditshwantsho ka botlalo bakeng sa tekanyo ya mosebetsi le mothamo ka hare ho thuto ya NM, ke ntho ya bohlokwa, mme mekgwa ya Monte Carlo (MC) e sebedisitswe ka katleho bakeng sa boiteko bona. Ho feta mona, mothamo o feletseng wa tekanyetso ya MC o amohetswe ke ba bangata e le boemo bo amohelehileng ka ho fetisisa ba boemo ba kgauta ebile e le mokgwa o nepahetseng ka ho fetisisa wa tekanyo ya mothamo bakeng sa mothamo o lokiseditsweng mokudi ka ho qolleha wa patient-specific dosimetry. MC simulations di fana ka monyetla wa ho ba le boemo ba kgauta oo ka ona ho ka bapiswang mothamo bakeng sa ho hlahlojwa. Ka hona diphuputso tsena di reretswe ho hlahloba ho lekanya ka nepo ha 177Lu SPECT le mothamo o lokiseditsweng mokudi ka ho qolleha ka ho sebedisa MC simulations. Taba ya sehlooho e ne e le ho totobatsa kabo ho ya ka mmele ya 177LuDOTATATE ho ya ka ho tshwaneleha ha yona ho bakudi ba RPT ba nang le dihlahala tsa metastasised neuroendocrine. Diphiyo tse ditho tse kginang mothamo bakeng sa RPT le 177Lu-DOTATATE. Diphuputso di bontshitse hore methamo bakeng sa diphiyo e fapana haholo pakeng tsa bakudi. Ha o tadima kamano pakeng tsa mothamo o nkilweng bakeng sa hlahala le mothamo wa phokotso ya hlahala, bakeng sa tekolo e phethahetseng ya bohlwahlwa kapa matla, methamo e amohetsweng e lokela ho lekanywa eseng feela bakeng sa diphiyo empa, haeba ho kgoneha, esita le ho dihlahala. Diphuputso tsena di kenyeleditse voxel-based phantoms tse tswang ho phantom le patient CT data e le ho phethahatsa virtual image-based activity quantification le methamo ka ho sebedisa MC simulations. Voxel-based phantoms di fetotswe ho kenyeletsa dipopeho tse etsisang dihlahala. Sepheo sa pele sa diphuputso tsena e bile ho nnetefatsa mokgwa wa Siemens Symbia T16 dual-head SPECT/CT gamma camera e fumanehang tleliniking ya rona ka ho sebedisa lenaneo la SIMIND MC bakeng sa setshwantsho sa 177Lu. Nnetefatso ena e fihleletswe ka ho bapisa mokgwa wa teko le simulated gamma camera iii performance planar le diteko tsa mokgwa wa SPECT. Diphetho di ne di dumellana hantle mme di fane ka kgothatso e lekaneng ya hore SIMIND e ka etsisa Symbia T16 ka katleho mme ebe e sebediswa bakeng sa diphuputso tse ding tse tlang tsa 177Lu SPECT/CT image quantification. Sepheo sa bobedi se entse diphuputso tsa ditlamorao tsa sphere and cylinder calibration factor (CF) geometries esita le tse amanang le tsona e leng recovery coefficients (RCs) bakeng sa nepahalo ya 177Lu SPECT images ka ho sebedisa MC simulations. Dipatlisiso di entswe ka ho sebedisa geometries of a cylindrical, an anthropomorphic torso, le patient-specific phantoms. Tekanyetso ya bongata e nepahetseng e ile ya hlahlojwa bakeng sa dihlahala le diphiyo. Diphetho di bontshitse hore 177Lu SPECT quantification accuracies di kgema ka ho lekana ka katleho le sphere-based and cylinder-based CF le RC combinations moo ditokiso tsohle tsa SPECT di entsweng. Tekanyo e ikgethang ka nepo ya ≤ 3.5% e kgema ka ho tshwana le diphihlello tsa dingolwa mme e loketse ditshwanelo tsa 5% bakeng sa mothamo o lekaneng ka nepo. Sepheo sa boraro sa diphuputso se reretswe ho bapisa nepahalo ya methamo e amohetsweng e ngodisitsweng ka softewere ya LundADose and OLINDA/EXM 1.0 ka ho sebedisa three patient-specific voxel-based phantoms. Nepahalo kapa tekanyo e nepahetseng ya mothamo e ile ya hlahlojwa ka ho bapisa methamo e ngodisitsweng ho ditshwantsho tsa “nnete” tsa mesebetsi e kopantsweng le tekanyetso ya MC e feletseng e le ho hlalosa boemo ba kgauta. Tekanyo e nepahetseng pakeng tsa LundADose (6.6%) le OLINDA/EXM 1.0 (8.1%) e ne e ka bapiswa. Tekanyo e nepahetseng ya ≤ 10% e bontshitse hore dipolatefomo tsa softewere di batla di atametse ho ditekanyetso tsa nnete tsa mothamo mme di kgothaletsa hore tekanyo e nepahetseng ya mothamo e ka tshetjwa ka botlalo.

Umgomo we-radiopharmaceutical therapy (RPT) uwukuletha umthamo omkhulu kumathumba anomdlavuza kuyilapho usindisa izicubu ezinempilo. Ngokufanelekile, i-radiopharmaceutical kufanele inqwabelane esicutshini esinamathumba futhi imisebe imuncwe ngokuphelele ukuze kubhujiswe izicubu; nokho, akunjalo. I-Dosimetry ilwela ukulinganisa ukusebenza kahle kokuletha umthamo omkhulu kumaseli esimila anobuthi obuncane esicutshini esinempilo. I-dosimetry eqondene nesiguli inikeza amandla okuthi i-RPT ifinyelelise amandla ayo aphelele njengokwelashwa okusekelwe ngokunemba okunamandla. Imizamo ye-dosimetry eqondene nesiguli ihlala iyinselele ngenxa yezinyathelo ezihlelekile ekuhambeni komsebenzi we-dosimetry yomtholampilo. I-SPECT/CT imaging ivumela ukulinganiswa kokusatshalaliswa kwe-bio-kinetic kwemithi ye-radiopharmaceuticals ngokunemba okuhle, okudingekayo ku-dosimetry enembile. Isofthiwe ye-dosimetry ehlukene iyatholakala (eyokuthengisa futhi engeyona eyentengiso), kodwa lezi kufanele zibekwe uphawu ngaphambi kokuthi zisetshenziswe. Ukuthuthukisa inqubo yokucabanga yokulinganisa umsebenzi kanye ne-dosimetry kumkhakha we-NM kubalulekile, futhi amasu e-Monte Carlo (MC) asetshenziswe ngempumelelo kulo mzamo. Ngaphezu kwalokho, i-dosimetry ye-MC ephelele yazuza ukwamukelwa okubanzi njengezinga legolide kanye nezindlela ezinembe kakhulu ze-dosimetry eqondene nesiguli. Ukulingisa kwe-MC kunikeza inzuzo yokuba nezinga legolide lapho i-dosimetry ingalinganiswa khona, futhi kuhlolwe ukunemba kwe-dosimetry. Ngakho-ke lo mqulu uhlose ukuhlola ukunemba komthamo womsebenzi we-177Lu SPECT kanye ne-dosimetry eqondene nesiguli kusetshenziswa ukulingisa kwe-MC. Bekugxilwe ekusatshalalisweni kwe-bio ye-177LuDOTATATE ngenxa yokufaneleka kwayo emtholampilo ku-RPT yeziguli ezinezimila ze-neuroendocrine ze-metastasised. Izinso yizitho ezinciphisa umthamo we-RPT ene-177Lu-DOTATATE. Ucwaningo lubonise imithamo yezinso ukuthi ihluke kakhulu phakathi kweziguli. Uma kubhekwa ukuhlobana phakathi kwethamo elimuncwa isimila kanye nokunciphisa isimila, ukuze kuhlolwe ukusebenza kahle okuphelele, imithamo emuncwayo akufanele inqunyelwe izinso kuphela kodwa, lapho kungenzeka khona, inwetshelwe ezimila. Lolu cwaningo luhlanganise ama-phantom asuselwa ku-voxel akhiqizwe ku-phantom nedatha ye-CT yesiguli ukuze enze ukulinganisa komsebenzi okususelwe ezithombeni kanye ne-dosimetry kusetshenziswa ukulingisa kwe-MC. Ama-phantom asuselwa ku-voxel ashintshiwe ukuze afake izakhiwo eziyindilinga ezilingisa amathumba. Injongo yokuqala yalolu cwaningo bekuwukuqinisekisa imodeli yekhamera ye-Siemens Symbia T16 enekhanda elikabili SPECT/CT etholakala emtholampilo wethu kusetshenziswa uhlelo lwe-SIMIND MC lwe-177Lu imaging. Ukuqinisekisa kufinyelelwe ngokuqhathanisa iplani yokusebenza yekhamera ye-gamma yokuhlola nefanisiwe kanye nokuhlolwa kwemibandela ye-SPECT. Imiphumela yayivumelana kahle futhi yanikeza ukuzethemba okwanele kokuthi i-SIMIND ingakwazi ukulingisa i-Symbia T16 ngempumelelo futhi isetshenziselwe uphenyo oluqhubekayo lwe-177Lu SPECT/CT yokulinganisa isithombe. Umgomo wesibili uphenye umthelela we-sphere kanye ne-cylinder calibration factor (CF) geometries kanye nama-coefficients awo okubuyisela ahambisanayo (RCs) ekunembeni kokulinganisa kwezithombe ezingu-177Lu SPECT kusetshenziswa ukulingisa kwe-MC. Uphenyo lwenziwa kusetshenziswa i-geometries ye-cylindrical, i-anthropomorphic torso, kanye nama-phantom aqondene nesiguli. Ukunemba kwe-quantification kwahlolelwa izimila nezinso. Imiphumela yabonisa ukuthi ukunemba komthamo okungu-177Lu SPECT kuqhathaniswe kahle nezinhlanganisela ze-CF ne-RC ezisekelwe kusilinda ezisuselwe kusilinda lapho zonke izilungiso ze-SPECT zisetshenziswa. Ukunemba okuphelele komthamo okungu-≤ 3.5% kuqhathaniswa kahle nokutholwe ezincwadini futhi kuthobelane nezimfuneko ezingu-5% ze-dosimetry enembile. Injongo yesithathu yomqulu ihlose ukuqhathanisa ukunemba kwemithamo emunyiwe ehlanganiswe nesofthiwe ye-LundADose kanye ne-OLINDA/EXM 1.0 kusetshenziswa ama-phantom amathathu asekelwe ku-voxel yesiguli. Ukunemba kwe-dosimetry kwahlolwa ngokuqhathanisa imithamo ebaliwe nezithombe zomsebenzi “zeqiniso” ezihlanganiswe ne-dosimetry egcwele ye-MC ukuze kuchazwe izinga legolide. Ukunemba phakathi kwe-LundADose (6.6%) ne-OLINDA/EXM 1.0 (8.1%) kuye kwaqhathaniswa. ≤ Ukunemba okungu-10% kwe-dosimetry kuphakamise ukuthi izinkundla zesofthiwe zilinganisele izilinganiso zomthamo wangempela futhi zakhuthaza ukunemba kwe-dosimetry ukuthi kwethembeke.
Thesis (Ph.D.(Medical Physics))--University of the Free State, 2021
Keywords: Monte Carlo; SIMIND; Lutetium-177; SPECT; Activity Quantification; Calibration; Factor; Recovery Coefficient; Dosimetry Accuracy; Patient-specific Phantom; Voxel-based phantom